Effects of Clinical Mastitis on Reproductive Performances in Dairy Cows (Journal of Science and Technology Research, 2024)
The study was undertaken to study the productive and reproductive performances in clinical mastitis (CM) affected and apparently, healthy dairy crossbred cows and to analyze the effects of mastitis considering age, lactation, and severity of mastitis on reproductive performances in crossbred cows. A survey using a questionnaire was done to record different parameters of the cows during the period November 2021 to March 2022. A total of 58 lactating cows included in this study were divided into two groups named mastitis (n=24) and controlled (n=34). Cows of the mastitis groups were divided into subgroups depending on the age, lactation number and severity of mastitis. Prolactin (PRL), progesterone (P4) and estrogen (E2) levels of cows at the time of AI  were analyzed. The results showed that cows of the mastitis group had substantially (P8 for Milking Yield (16.21±2.39 Lt), Days to first heat detection after parturition (109.29±13.57), Days to first insemination following parturition (122.14±15.87), and Days open (165.79±16.70), and in cows of Sub-group 7-8 had for the Days of incidence of mastitis following parturition (51.57±12.73). Considering the number of lactations,  we observed the highest values of  Milking Yield (16.69±2.20 Lt), Days to first heat detection after parturition (108.75±11.58), Days to first insemination following parturition (120.00±13.96), and Days open (160.63±15.20) in cows of Sub-group lactation number >3 and the highest Days of occurrence of mastitis after parturition in cows of Sub-group lactation number 3.  Based on the degree of clinical mastitis, it was found that cows of the severe mastitis sub-group had the greatest Milking Yield (24.80±5.40 Liter) at a significant level (P0.05) variation observed in different parameters in terms of reproductive performances in all sub-groups. In addition, significantly (P